CFD preliminary assessment of a protrusions based facility. (June 2018) - Borreani, Walter; Devia, Francesco; Lomonaco, Guglielmo; Marchitto, Annalisa
Highlights: Experimental and numerical analyses of protrusions in header for water flow are shown. The header geometry influence on the maldistribution of the two-phase flow is studied. An experimental facility for water-air flow in headers with protrusions is shown. Some turbulence models are compared for various flow rates and protrusions geometries. The detailed data concerning the numerical procedure are provided. Abstract: The design of compact heat exchangers and their mass flow distributors is still based on empirical approaches and both numerical analyses and experimentations are needed for designing the best geometries useful to reduce the mass flow rate non uniformities in parallel channels. As known, this is indeed a cause of reduction in both thermal and fluid-dynamic performances. In this paper a series of single-phase CFD simulations on water and water with air injection are carried out in order to estimate the capabilities of the solvers implemented in the OpenFOAM code to reproduce (in comparison with experimental data) such kind of configurations and phenomena. The effects of different turbulence models (both RANS and LES) implemented in OpenFOAM are investigated; additionally some general considerations on the differences and analogies among different Reynolds numbers flow and turbulence model effects applied to the present configuration are discussed. Finally, the capability of the code to reproduce the peculiar behaviour of a protrusions based experimental facility is investigated, with the aim of obtaining an acceptable simulation of the non-uniform mass flow distribution in each protrusion. The present paper is an extended version including the main conclusions and observations emerged in the 2nd AIGE-IIETA International Conference in Genoa.